British music, musicians and institutions, c.1630-1800 : essays in honour of Harry Diack Johnstone - Lynan, Peter; Rushton, Julian (Music in Britain, 1600-2000., 2021)
Building upon the developing picture of the importance of British music, musicians and institutions during the eighteenth century, this book investigates the themes of composition, performance (amateur and professional) and music-printing, within the wider context of social, religious and secular institutions.